Knowledge and attitude regarding COVID-19 among students from multiple professional background in Riyadh Region, Saudi Arabia: A cross-sectional study - Rajashekhara Bhari Sharanesha; Bader Khalid Aljuai; Tariq Ahmed Alfaifi; Abdulelah M Shukr; Mohammed Abdullah Bamuqadm; Abdulmalik Abdullah Alhoti (Wolters Kluwer Medknow Publications, 2021)
Introduction: Coronavirus disease 2019 is abbreviated as "COVID-19" caused by the severe acute respiratory syndrome-corona virus 2 first emerged in Wuhan, China, on December 2019. On 15th of March, this disease has been classified by the World Health Organization as a pandemic and a global public health emergency. Objective: The study's aim was to evaluate the knowledge and behavior toward the virus among professional students of Riyadh, Saudi Arabia. Methodology: A cross-sectional study done on 753 students which were invited to complete a Google document using a 20-item electronic questionnaire that was design to gauge knowledge and attitude toward COVID-19. The study was conducted from February 20 to March 18, 2020 in Alkharj and Riyadh region. Results: The predominant sex is male (73%), the common age is <25 years old, more medical students were involved in the study than any other specialty and the predominant educational degree of the participants was bachelors. The awareness of mode of transmission of novel coronavirus infection is less in business administration participants compare to others and is highly significant (P ˂ 0.001). Most of the participants (588 [98%]) were aware of coronavirus but only 302 (50%) of respondents are aware of COVID-19 which is highly significant (P ˂ 0.001). Conclusion: The results are mostly uniform among different professional students with the exception of some knowledge-related questions. The Internet was the main source of information, so there is a need to create more awareness about COVID-19 through social media.